Life Beyond PTF: Invited talk. Issue Volume 14:Issue S339(2018) (November 2017) - Bellm, E. C.
Abstract: In March 2017, the Intermediate Palomar Transient Factory (iPTF) ceased operations. This Symposium was an appropriate opportunity to review the scientific returns from iPTF and its predecessor survey, the Palomar Transient Factory (PTF), and to summarise the lessons learned. Succeeding iPTF on the Palomar Observatory 48-inch Schmidt telescope is the Zwicky Transient Facility (ZTF), a new survey with an order of magnitude faster survey speed that is now being commissioned. I described the design and scientific rationale for ZTF. ZTF is prototyping new alert stream technologies being explored by the Large Synoptic Survey Telescope (LSST) to distribute millions of transient alerts per night to downstream science users. I described the design of the alert system and discussed it in the context of the wider LSST and community broker ecosystem.